How does climate change alter agricultural strategies to support food security? - Lipper, Leslie; Thornton, Philip K. (2013)
Priorities for Public Sector Research on Food Security and Climate Change, Report presentation by Leslie Lipper, FAO and Philip Thornton, ILRI on April 12, 2013 at the Food Security Futures Conference in Dublin, Ireland.